Camarillo State Hospital Governor's Council Report - F.H. Garrett:::::: (1960)
This five page document is another governor's council report for the month of October written by F.H. Garrett, to discuss certain topics that pertain to the Camarillo State Hospital. The first issue is personnel problems as a result of the new admission procedure, several wards have shown a stress situation this past month because of being short-staffed. The second issue is the rehabilitation services which has scheduled two concerts in Hagerty Auditorium where singers and musicians will be performing for our patients, which are hoped to be greatly enjoyed by the patients. The third issue discussed in this governor's council report is the convalescent leave psychiatrist program which the Camarillo State Hospital has no full-time psychiatrist in the program impeding it from functioning well.